Digital Marketing of Banking Products: The Role of Brand Image and Promotion in Shaping Customer Loyalty at BRI in Medan City - Fitra Arlina Nasution; Dewi Nurmasari Pane (PT. INOVASI TEKNOLOGI KOMPUTER, 2026)
Digital transformation has significantly reshaped marketing strategies in the banking sector. This study examines the effect of Digital Marketing on Customer Loyalty, with Brand Image and Promotion as mediating variables, in the context of Bank Rakyat Indonesia (BRI) in Medan City. A quantitative explanatory research design was employed using a sample of 100 banking customers selected through purposive sampling. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results indicate that Digital Marketing significantly influences Brand Image, Promotion, and Customer Loyalty. Furthermore, Brand Image and Promotion partially mediate the relationship between Digital Marketing and Customer Loyalty. The structural model explains 63% of the variance in Customer Loyalty. The findings highlight the strategic role of integrated digital marketing initiatives in strengthening brand perception and enhancing long-term customer loyalty in the banking industry.